The embryogenesis of the equine femorotibial joint: The equine interzone. (10th September 2014) - Jenner, F.; van Osch, G. J. V. M.; Weninger, W.; Geyer, S.; Stout, T.; van Weeren, R.; Brama, P.
Summary Reasons for performing study Articular cartilage regeneration is the focus and goal of considerable research effort. Since articular chondrocytes descend from a distinct cohort of progenitor cells located in embryonic nascent joints (interzones), establishing the timing of equine interzone formation is an essential first step towards understanding equine joint and articular cartilage development. Objectives To establish the time frame during which the equine femorotibial interzone forms. Study design Descriptive anatomical study. Methods Equine embryos were harvested at 37 (E37), 40, 42, 45, 50 and 65 days' gestation. The femorotibial interzone was examined using high‐resolution episcopic microscopy of E37, E42, E45, E50 and E65. Additional histology and collagen‐II‐immunohistochemistry were performed on E42. Results At E37, the femorotibial interzone is first visible as a uniform layer, while at E42 the interzone is fully formed and consists of 3 morphologically distinct layers. The first evidence of cavitation was seen at E45. At E50, the cruciate ligaments were well formed and by E65, joint formation appeared complete. Conclusions The embryogenesis of the equine femorotibial joint is similar to the developmental timeline of stage‐matched human and murine embryos. Further studies looking at interzone formation on a cellular and molecular level may further our understanding of the intricate developmental patterns and pathways of articular cartilage development.